(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2020)
The dream of authenticity, the savage sensibility, the idea that “modernity” – however meant – was a theme of very limited interest for anthropologists is a mark of the Western history of cultural analysis throughout a good part of the last century. Still today it remains in some not always marginal lines of western ideology with regard to other people and other places (exotic places, ethnic objects, strange rituals), as well as in a certain persistent conception of cultural anthropology such as a search for authentic cultural richness. In this paper, I concisely present the main lines of the authenticity debate and argue for a hybrid (and oxymoronic) notion of cultural authenticity focusing on an ethnographic case.